2015
DOI: 10.1002/etc.3233
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing human pharmaceuticals for ecological risks in the freshwater environment of Korea

Abstract: Pharmaceutical residues are potential threats to aquatic ecosystems. Because more than 3000 active pharmaceutical ingredients (APIs) are in use, identifying high-priority pharmaceuticals is important for developing appropriate management options. Priority pharmaceuticals may vary by geographical region, because their occurrence levels can be influenced by demographic, societal, and regional characteristics. In the present study, the authors prioritized human pharmaceuticals of potential ecological risk in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The range of possible WWTP removal estimates were used to calculate a possible PEC range. Second, data gaps were filled using the USEPA's EPISuite software STPWIN program , similar to a recent prioritization exercise in Asia .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of possible WWTP removal estimates were used to calculate a possible PEC range. Second, data gaps were filled using the USEPA's EPISuite software STPWIN program , similar to a recent prioritization exercise in Asia .…”
Section: Methodsmentioning
confidence: 99%
“…The derivation of PECs is typically based on data for pharmaceutical usage, degree of metabolism in humans, removal in wastewater treatment plants (WWTP), and environmental dilution. The method most commonly used is based on the approach recommended in the European Medicines Agency (EMEA) guidelines for assessment of the risk of human pharmaceuticals in the environment [6,9,[17][18][19][20][21][22][23]. Default parameters (e.g., for dilution of wastewater by the receiving water) proposed by the EMEA guidance are regularly used in these prioritization exercises, regardless of their suitability [6,10,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…The average concentration of metformin in raw waste waters exceeds the concentrations of other pharmaceuticals by roughly two orders of magnitude (Oosterhuis et al 2013). Recent studies conducted on US streams (Bradley et al 2017), waste waters in Greece (Kosma et al 2015), subarctic locations in Faroe Islands, Iceland, and Greenland (Huber et al 2016), and freshwater environment in Korea (Ji et al 2016) and Vietnam (Chau et al 2015) showed that metformin is one of the 10 most frequently detected designed bioactive contaminants. Data on the levels of metformin and its metabolite, guanylurea, show that the threshold of toxicological concern is exceeded 5-10 times in EU surface waters (European Environment Agency 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prioritization strategies is one area that has received considerable attention in the present special issue and elsewhere in the literature, with a number of articles proposing risk‐based approaches, taking into account not only anticipated exposure levels but also the relative potency of the compounds . Despite some differences in the composition of prioritization lists, the represented pharmaceutical classes overlap and include antibiotics, selective serotonin reuptake inhibitors (SSRIs), antidepressants, endocrine active pharmaceuticals, and nonsteroidal anti‐inflammatory drugs.…”
Section: The Second Special Issue—where We Have Come From and Where mentioning
confidence: 99%